A Smart Taxation for Sustainable Tourism: A Policy Approach to Addresing Overtourism - Edison, (Journal of Vocational Innovation, Achievement and Education, 2025)
This research analyzes the implementation of smart taxation as an innovative policy approach to address overtourism and achieve sustainable tourism development. Descriptive qualitative methodology with multi-destination comparative studies was employed to identify effective mechanisms within intelligent taxation systems. Results demonstrate that technology-based tariff differentiation effectively optimizes tourism economic contributions while mitigating negative environmental and social impacts. Implementation of artificial intelligence and blockchain technology facilitates personalized taxation structure alignment with tourists' ecological footprints. Transformation from quantity-oriented toward quality-focused tourism development generates enhanced destination competitiveness and stakeholder satisfaction. Smart taxation proves effective as a policy instrument for achieving optimal balance between economic growth, environmental preservation, and social welfare within the tourism industry. Comprehensive policy framework with integrated multi-stakeholder approach is essential for optimizing sustainable taxation system implementation.